2022
DOI: 10.1158/1535-7163.mct-20-1103
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitizing Pancreatic Cancer via Effective Autophagy Inhibition

Abstract: Despite aggressive treatments, pancreatic ductal adenocarcinoma (PDAC) remains an intractable disease, largely because it is refractory to therapeutic interventions. To overcome its nutrient-poor microenvironment, PDAC heavily relies on autophagy for metabolic needs to promote tumor growth and survival. Here, we explore autophagy inhibition as a method to enhance the effects of radiotherapy on PDAC tumors. Hydroxychloroquine is an autophagy inhibitor at the focus of many PDAC clinical trials, including in comb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…M-LIP-CLT, a hybrid nanoplatform capable of fusing Celastrol (CLT)-Loaded PEGylated lipids with the DC2.4 cell membrane, is an effective drug delivery system for PDAC-targeted therapy [ 91 ]. EAD1 is a synthesized analogue of hydroxychloroquine (HCQ) that is found to make KRAS-mutant PDAC more sensitive to radiotherapy [ 92 ]. A study reported that cetuximab (CTX)-conjugated maleimide-polyethylene glycol-chlorin e6 (CMPC) is an immune-stimulating antibody-photosensitizer conjugate, and it can be used for KRAS-mutant PDAC, the mechanism of which is Fc-mediated dendritic cell phagocytosis and immunogenic cell death triggered by light [ 93 ].…”
Section: Therapeutic Strategies In Kras-mutant Cancersmentioning
confidence: 99%
“…M-LIP-CLT, a hybrid nanoplatform capable of fusing Celastrol (CLT)-Loaded PEGylated lipids with the DC2.4 cell membrane, is an effective drug delivery system for PDAC-targeted therapy [ 91 ]. EAD1 is a synthesized analogue of hydroxychloroquine (HCQ) that is found to make KRAS-mutant PDAC more sensitive to radiotherapy [ 92 ]. A study reported that cetuximab (CTX)-conjugated maleimide-polyethylene glycol-chlorin e6 (CMPC) is an immune-stimulating antibody-photosensitizer conjugate, and it can be used for KRAS-mutant PDAC, the mechanism of which is Fc-mediated dendritic cell phagocytosis and immunogenic cell death triggered by light [ 93 ].…”
Section: Therapeutic Strategies In Kras-mutant Cancersmentioning
confidence: 99%
“…Currently, CQ and HCQ have been approved by the FDA for rheumatoid arthritis, malaria and assessed in a range of clinical trials involving cancer treatment [ 330 , 331 ]. Interestingly, there is a recent report of a novel, more efficacious analog, EAD1, capable of increasing the sensitivity of PDAC neoplasms and stem cells to radiation therapy [ 332 ]. Additionally, EAD1 was shown to be more efficacious in KRAS G12D mutant cell lines, indicating its potential as a treatment option for PDAC [ 332 ].…”
Section: Inhibiting Autophagic Machinerymentioning
confidence: 99%
“…Interestingly, there is a recent report of a novel, more efficacious analog, EAD1, capable of increasing the sensitivity of PDAC neoplasms and stem cells to radiation therapy [332]. Additionally, EAD1 was shown to be more efficacious in KRAS G12D mutant cell lines, indicating its potential as a treatment option for PDAC [332]. The study by Wolpin et al demonstrated that HCQ as a monotherapy against chemoresistant PDAC patients was inconsistent and inefficacious [333].…”
Section: Targeting Late-stage Autophagymentioning
confidence: 99%
“…The autophagy-related genes, especially ATG5 play a critical role in the EMT process as indicated by a study on cervical cancer cells ( 119 ). In radio-resistant cancer cells, like pancreatic ductal adenocarcinoma cells and NSCLC stem cells, autophagy has found to be essential in promoting tumor growth and invasiveness ( 120 ) as well as maintaining the stem cell-like properties ( 121 ) of the cells. as a result autophagy inhibitors, either individually or with combination with other traditional methods of cancer therapy, have been able to block proliferation, colony and, spheroid formation (in pancreatic CSC populations) in cancer cells ( 122 ).…”
Section: Influence Of Autophagy On Radiation Response Of Tumorsmentioning
confidence: 99%